Dual function of a bumblebee (Bombus ignitus) serine protease inhibitor that acts as a microbicidal peptide and anti-fibrinolytic venom toxin. (October 2022) - Kim, Bo Yeon; Kim, Yun Hui; Park, Min Ji; Yoon, Hyung Joo; Lee, Kyeong Yong; Kim, Hye Kyung; Lee, Kwang Sik; Jin, Byung Rae
Abstract: In bee venoms, low–molecular-weight peptides, including serine protease inhibitors (SPIs), exhibit multifunctional activities. Although SPIs in bee venoms are relatively well known, those that function in both the body and secreted venom of bees are not well-characterized. In this study, we identified a bumblebee ( Bombus ignitus ) SPI (BiSPI) that displays microbicidal and anti-fibrinolytic activities. BiSPI was found to consist of a trypsin inhibitor–like domain containing a P1 site and ten cysteine residues. We observed that the BiSPI gene was ubiquitously transcribed in the body, including the venom glands. In correlation, the BiSPI protein was detected both in the body and secreted venom by using an antibody against a recombinant BiSPI peptide produced in baculovirus-infected insect cells. Recombinant BiSPI exhibited inhibitory activity against trypsin but not chymotrypsin and inhibited microbial serine proteases and plasmin but not elastase or thrombin. Moreover, recombinant BiSPI recognized carbohydrates and bound to fungi and gram-negative and gram-positive bacteria. Consistent with these properties, recombinant BiSPI exhibited microbicidal activities against bacteria and fungi through induction of structural damage by binding to the microbial surfaces. Additionally, recombinant BiSPI inhibited the plasmin-mediated degradation of human fibrin and was thus concluded to exhibit anti-fibrinolytic activity. Moreover, the peptide showed no effect on hemolysis. These findings demonstrate the dual function of BiSPI, which acts as a microbicidal peptide and anti-fibrinolytic venom toxin. Highlights: Bombus ignitus serine protease inhibitor (BiSPI) functions in the body and secreted venom. BiSPI inhibits microbial serine proteases and exhibits bactericidal and fungicidal activities. BiSPI functions as a plasmin inhibitor with anti-fibrinolytic activities. BiSPI acts as a microbicidal peptide and anti-fibrinolytic venom toxin.